2020
DOI: 10.1111/ene.14174
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in Alzheimer’s disease: current challenges and implications for clinical practice

Abstract: Alzheimer's disease (AD) is characterized by high heterogeneity in disease manifestation, progression and risk factors. High phenotypic variability is currently regarded as one of the largest hurdles in early diagnosis and in the design of clinical trials; there is therefore great interest in identifying factors driving variability that can be used for patient stratification. In addition to genetic and lifestyle factors, the individual's sex and gender are emerging as crucial drivers of phenotypic variability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 169 publications
2
53
1
Order By: Relevance
“…This finding suggests that the mechanism underlying the transport of plasmalogens from the plasma to the brain is more active in young individuals and in some males. This may be relevant to the fact that elderly individuals, and particularly females, have a higher risk for Alzheimer’s disease [ 31 ]. Thus, plasmalogen transport from the plasma to the brain may be one of the factors regulating the development of plasmalogen-dependent brain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the mechanism underlying the transport of plasmalogens from the plasma to the brain is more active in young individuals and in some males. This may be relevant to the fact that elderly individuals, and particularly females, have a higher risk for Alzheimer’s disease [ 31 ]. Thus, plasmalogen transport from the plasma to the brain may be one of the factors regulating the development of plasmalogen-dependent brain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As the association between cognitive performance and risk of Alzheimer's disease and related dementias is well established, 9 disparities between sexes in education are thus a potential pathway through which differences between sexes in the risk of Alzheimer's disease and related dementias are generated. 2 , 3 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…33 On the other hand, the potential bene ts of HRT to prolong estrogen supply in older women have not been corroborated by interventional studies, 34,35 while the observational evidence remains con icting. 4,[36][37][38][39] The Women's Health Initiative Study (WHIS), is the only clinical trial that evaluated postmenopausal hormone therapy on preventing dementia, concluded that the risk of dementia was doubled in women randomised to estrogen-progestin based HRT. 34 In a case-control study in Finland, long-term use of systemic HRT was associated with an increased risk of Alzheimer's disease.…”
Section: Exogenous Hormone Usementioning
confidence: 99%
“…3 While the risk of developing dementia increases with age, the extent to which the female predominance is simply due to women's longer lifespan remains far from conclusive, and femalespeci c reproductive factors may be able to explain these sex disparities. 4,5 Several endogenous estrogen changes occur throughout a woman's reproductive life. Estradiol (E2) is the most predominant form of estrogen during reproductive life (from menarche to menopause) 6 and estriol (E3) is the primary estrogen during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation